Theoretical investigation of an acid catalyst for viable release of H2 from BN nanotubes: A local pair natural orbital coupled cluster approach. Issue 15 (30th April 2020) - Roy, Lisa
Abstract: Catalytic removal of H2 from boron‐nitride (BN)‐based nanomaterials at ambient conditions is of paramount importance in order to develop lightweight hydrogen storage media. Here, the DLPNO‐CCSD(T) technique is used to calculate accurate relative energies and activation barriers of Brønsted acid‐initiated removal of H2 from hydrogenated BN nanotubes (HBNNTs) with six different acids. Three crucial steps are identified in the mechanism: first H2 release, catalyst regeneration via proton transfer, and second H2 release to ensure feasibility of the dehydrogenation proposal. Our computational studies reveal that sulfonic acids with appropriate electrophilicity can facilitate dehydrogenation of HBNNT at a low free energetic cost (∆G ‡ = 17 kcal/mol). Importantly, these findings illustrate the possibility of H2 release from BN nanomaterials at ambient conditions and provides hope for a sustainable chemical hydrogen storage strategy. Abstract : Theoretical investigations demonstrate plausible dehydrogenation of chemisorbed hydrogen on BN nanotubes and the release of H2 molecules, at room temperature‐surmountable barriers, with properly screened Brønsted acid catalyst.